A chironomid-inferred summer temperature reconstruction from subtropical Australia during the last glacial maximum (LGM) and the last deglaciation. (15th August 2015) - Chang, Jie Christine; Shulmeister, James; Woodward, Craig; Steinberger, Lincoln; Tibby, John; Barr, Cameron
Abstract: A chironomid-based mean February temperature reconstruction from Welsby Lagoon, North Stradbroke Island, Australia covering the last glacial maximum (LGM) and deglaciation (between c. ∼23.2 and 15.5 cal ka BP) is presented. Mean February temperature reconstructions show a maximum inferred cooling of c. ∼6.5 °C at c. ∼18.5 cal ka BP followed by rapid warming to near Holocene values immediately after the LGM. The inferred timing, magnitude and trend of maximum cooling and warming display strong similarities to marine records from areas affected by the East Australian current (EAC). The warming trend started at c. ∼18.1 cal ka BP and is consistent with the start of deglaciation from Antarctic records. Near Holocene values are maintained through the deglaciation to 15.5 cal ka BP. These records suggest that changes in the Australian subtropics are linked to southern high latitudes. Highlights: A chironomid-based summer temperature reconstruction from Australia. Reconstruction covers the LGM and part of deglaciation. Cooling is similar to that derived from nearby marine records. Deglaciation is synchronous with Antarctica. Suggests climate link from Australian subtropics to high latitudes.